Anaerobic microbial corrosion of carbon steel under conditions relevant for deep geological repository of nuclear waste - Shrestha, Rojina; Černoušek, Tomáš; Stoulil, Jan; Kovářová, Hana; Sihelská, Kristína; Špánek, Roman; Ševců, Alena; Steinová, Jana (The Science of the total environment, 2021)
We examined microbial corrosion of carbon steel in synthetic bentonite pore water inoculated with natural underground water containing microorganisms over a period of 780-days under sterile and anaerobic conditions. Corrosion behaviour was determined using the mass loss method, SEM-EDS analysis and Raman spectroscopy, while qualitative and quantitative changes in the microbial community were analysed using molecular-biological tools (16S rDNA amplicon sequencing and qPCR analysis, respectively). Corrosion rates were significantly higher in the biotic environment (compared with an abiotic environment), with significant localisation of corrosion attacks of up to 1 mm arising within 12-months. Nitrate reducing bacteria, such as Pseudomonas, Brevundimonas and Methyloversatilis, dominated the microbial consortium, the high abundance of Methyloversatilis correlating with periods of highest localised corrosion penetrations, suggesting that this bacterium plays an important role in microbially influenced corrosion. Our results indicate that nitrate-reducing bacteria could represent a potential threat to waste canisters under nuclear repository conditions.
Keywords: Microbiological corrosion; koroze; Corrosion; Carbon steel; Nitrates; Anaerobiosis; ocel; radioaktivní odpad; Methyloversatilis; anaerobióza; Steel; Carbon; uhlík; Nuclear waste repository; Radioactive Waste; Nitrate-reducing bacteria